Doses de potássio em cobertura na primeira soca da cultura da cana-de-açúcar cultivada no norte matogrossense - Caione, Gustavo [UNESP]; da Silva, Amilton Ferreira [UNESP]; dos Reis, Luis Lessi [UNESP]; Dalchiavon, Flávio Carlos [UNESP]; Teixeira, Matheus Thiago Ramos; Santos, Pablo Aramís (My University, 2011)
The sugar cane crop has been cultivated in all regions of the Brazil, occupying different soil types. The north region of Mato Grosso has favorable climate conditions for the culture, however, has been achieved low productivity due to the not application of fertilizer and inefficient doses. Being the potassium the mineral element absorbed in large amount by culture. Aimed to with this work to evaluate the effect of growing doses of the nutrient applied in coverage in the second cycle of the variety of sugar cane IAC86-2480. The experimental design was randomized blocks, with four replications. The Potassium doses were: 0; 60; 120; 180 e 240 kg ha -1 of K 2O. Was evaluated the °Brix, diameter, weigth, height and productivity of stalk. No was significant effects for the variable °Brix in response to potassium doses, since to others had response quadratic. The dose of maximum agronomic efficiency was of 150 kg ha -1 de K 2O obtaining productivity of 85 t ha -1 of stalk, representing 25% increase in productivity.
Doses of potassium in coverage in the first cane ratoon of sugar cane crop cultivated in north matogrossense
Keywords: Agronomic efficiency; Cane ratoon; Productivity; Saccharum spp